Biotechnology and biological diversity: a challenge for education inthe network society - Rech, Aline Pereira de Arruda; Medeiros, Liziany Müller; Rosa, Luis Henrique Carvalho; Lima, Andréia Lucimar Silva de; Bedin, Daiane Teresa; Ribeiro, Ezequiel Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The text aims to analyze the relationship of biotechnology and biodiversity bio piracy as a problem for today's society. For this was held a brief explanation of the definitions and their relationships with technology and education. Conclusions as stated the need to provide education to society in order to contribute to making political, social and economic decisions that are in constant debate within society. Furthermore, the inclusion of technology education will lead society to understand the changes derived from biotechnology processes, and thus, accept or diverge with reasoned arguments and concrete. In view of this, there will be greater judicial control in biodiversity issues and the company will monitor the activities of multinationals in forests and will charge measures that enable awareness of a democratic, balanced and sustainable exploitation.